An Astronomical Diary or Almanack For the Year of Christian Aera 1787. Being the third Year after Bissextile or Leap Year, and the eleventh of the Independence of America. - Low, Nathanael, 1792-1883. (Tufts University. Tisch Library., 2018)
12 leaves. Tisch Library copy contains handwritten annotations.